Preparation and characterization of porous scaffolds based on poly(3-hydroxybutyrate) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) - Esmail, Asiyah (2022)
LA/P/0140/2020 iNOVA4Health/MULTI/04462/2018